2014
DOI: 10.1026/0049-8637/a000103
|View full text |Cite
|
Sign up to set email alerts
|

Versuch macht kluch g?!

Abstract: Fehler können wichtige Lernprozesse in Gang setzen, wobei entscheidend ist, wie Lernende mit Fehlern umgehen. In der vorliegenden Studie werden auf Individualebene Unterschiede zwischen Lernenden in zwei Aspekten des Umgangs mit Fehlern beschrieben, nämlich positive Hinwendung zu eigenen Fehlern (Fehlerlernorientierung, FLO) und angstvolle Vermeidung fehlerhafter Handlungen (Fehlerangst, FA). Auf Klassenebene werden Unterschiede zwischen Lernkontexten durch den schülerperzipierten Umgang der Lehrperson mit Feh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Four of the eight studies were conducted in the USA, one in Germany, one in Greece, and two in the UK. Two studies specifically reported on urban settings (Hargreaves & Affouneh, 2017; Kreutzmann et al, 2014) and one in which the majority of participants were from suburban settings (Kowalski & Froiland, 2020). All studies were conducted in mainstream primary/elementary schools, with three studies making specific reference to school type: private (LaBillois & Lagacé‐Séguin, 2007), public (Poulou et al, 2021), and state (Hargreaves & Affouneh, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four of the eight studies were conducted in the USA, one in Germany, one in Greece, and two in the UK. Two studies specifically reported on urban settings (Hargreaves & Affouneh, 2017; Kreutzmann et al, 2014) and one in which the majority of participants were from suburban settings (Kowalski & Froiland, 2020). All studies were conducted in mainstream primary/elementary schools, with three studies making specific reference to school type: private (LaBillois & Lagacé‐Séguin, 2007), public (Poulou et al, 2021), and state (Hargreaves & Affouneh, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Year groups recruited from schools ranged from Reception/Kindergarten to Year/Grade 6. One study (Kreutzmann et al, 2014) included older children up to 13 years old, but as the mean age reported was 10.79 years, it was still eligible to be included in our study. For those studies that reported on gender (Hughes & Coplan, 2018; Kowalski & Froiland, 2020; Kreutzmann et al, 2014; LaBillois & Lagacé‐Séguin, 2007), the male/female split was relatively even in all cases bar one (LaBillois & Lagacé‐Séguin, 2007) where 21 boys and 12 girls were included in the study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations